Analysis of carboxylesterase 2 transcript variants in cynomolgus macaque liver. (1st February 2019) - Uno, Yasuhiro; Igawa, Yoshiyuki; Tanaka, Maori; Ohura, Kayoko; Hosokawa, Masakiyo; Imai, Teruko
Abstract: Carboxylesterase (CES) is important for the detoxification of a wide range of drugs and xenobiotics. In this study, the hepatic level of CES2 mRNA was examined in cynomolgus macaques used widely in preclinical studies for drug metabolism. Three CES2 mRNAs were present in cynomolgus macaque liver. The mRNA level was highest for cynomolgus CES2A (formerly CES2v3), much lower for cynomolgus CES2B (formerly CES2v1) and extremely low for cynomolgus CES2C (formerly CES2v2). Most various transcript variants produced from cynomolgus CES2B gene did not contain a complete coding region. Thus, CES2A is the major CES2 enzyme in cynomolgus liver. A new transcript variant of CES2A, CES2Av2, was identified. CES2Av2 contained exon 3 region different from wild-type (CES2Av1). In cynomolgus macaques expressing only CES2Av2 transcript, CES2A contained the sequence of CES2B in exon 3 and vicinity, probably due to gene conversion. On genotyping, this CES2Av2 allele was prevalent in Indochinese cynomolgus macaques, but not in Indonesian cynomolgus or rhesus macaques. CES2Av2 recombinant protein showed similar activity to CES2Av1 protein for several substrates. It is concluded that CES2A is the major cynomolgus hepatic CES2, and new transcript variant, CES2Av2, has similar functions to CES2Av1.